Towards a theoretical framework for female IT professionals' advancement to IT executive positions : a South African perspective - Pretorius, H.W. (Herman Walter) (University of Pretoria, 2018)
The representation of female Information Technology Executives in South Africa is far from ideal. Research shows that there are more women in Information Technology management support functions than in leadership roles. Even though every year the total number of Information Technology Executives profiled has increased, from 153 in 2011 to 172 in 2016, only 10% average of them are female. This is despite women comprising the majority of South Africa’s population. Given the existence of female Information Technology Executives, albeit a few, this study discusses factors that contribute to the success of South African female Information Technology professionals in achieving Information Technology Executive positions, despite the challenges they are faced with. A qualitative research approach was followed in conducting the study. Data was gathered using semi-structured interviews with fifteen (15) South African female Information Technology Executives. The Individual Differences Theory of Gender and Information Technology was employed to understand each Information Technology Executive’s influence on her career progression. The results indicated the approximate age that female Information Technology professionals are likely to achieve Information Technology leadership levels. In addition, the results indicated the type of Information Technology management experience that is advantageous to female Information Technology professionals’ advancement to Information Technology Executive positions. Considering the masculine nature of the Information Technology field, the results further indicated the type of support structures that are valuable in manoeuvring through the Information Technology leadership labyrinth. The study also found that cultural beliefs were changing to accommodate and accept femininity within masculine roles. The study contributes to both academia and the Information Technology industry. First, Eileen Trauth’s Individual Differences Theory of Gender and Information Technology theory was used to understand how Information Technology career challenges faced by South African female Information Technology professionals could be overcome to reach Information Technology Executive positions. Secondly, the adoption of interpretive methods enabled an analysis of multiple case studies, thereby adding to the body of knowledge on women in Information Technology. Lastly, the research findings were used to develop a theoretical framework that female Information Technology professionals in South Africa could adopt on their career advancement journeys. This, in turn, may improve the representation of female Information Technology Executives in South Africa.